Asymmetric dimethylarginine serum levels are associated with early mortality after allogeneic stem cell transplantation - Radujković, Aleksandar; Rachakonda, P. Sivaramakrishna; Müller-Tidow, Carsten; Dreger, Peter; Luft, Thomas (Haematologica, 2019)
Increasing evidence suggests that endothelial cell distress is associated with mortality after allogeneic stem cell transplantation and acute graft-versus-host disease. Asymmetric dimethylarginine is an endogenous nitric oxide synthase inhibitor that induces endothelial cell dysfunction. We analyzed the impact of pre-transplant serum levels of asymmetric dimethylarginine on outcome after allogeneic stem cell transplantation. Since acute graft-versus-host disease and its treatment are major contributors to post-transplant mortality, the effect of asymmetric dimethylarginine on outcome measures was also assessed after onset of acute graft-versus-host disease. A total of 938 patients allografted at two centers between 2002 and 2013 were included in the retrospective study. In multivariable models, higher pre-transplant asymmetric dimethylarginine levels were significantly associated with an increased risk of non-relapse mortality (hazard ratio 1.43 per 1-log2 increase, P=0.005) but not with relapse (hazard ratio 1.21, P=0.109) within the first year after transplantation. This translated into worse overall survival (hazard ratio 1.45, P<0.0001) and shorter progression-free survival (hazard ratio 1.30, P=0.002) in the first year after transplantation. Higher pre-transplant asymmetric dimethylarginine levels were also associated with shorter overall survival (hazard ratio 1.46, P=0.001) and progression-free survival (hazard ratio 1.32, P=0.010) and higher non-relapse mortality (hazard ratio 1.36, P=0.042) within 1 year after the onset of acute graft-versus-host disease. Taken together, our data indicate an association between pre-transplant asymmetric dimethylarginine status and early non-relapse mortality in allografted patients, both overall and after the onset of acute graft-versus-host disease. These findings underline the relevance of endothelial dysfunction for transplant complications.
Gesehen am 22.05.2019